2009
DOI: 10.1194/jlr.m800345-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1-mediated cholesterol efflux generates microparticles in addition to HDL through processes governed by membrane rigidity

Abstract: ATP-binding cassette transporter A1 (ABCA1) mediates cholesterol efflux to lipid-poor apolipoprotein A-I (apoA-I) and generates HDL. Here, we demonstrate that ABCA1 also directly mediates the production of apoA-I free microparticles. In baby hamster kidney (BHK) cells and RAW macrophages, ABCA1 expression led to lipid efflux in the absence of apoA-I and released large microparticles devoid of apoB and apoE. We provide evidence that these microparticles are an integral component of the classical cholesterol eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 47 publications
5
55
0
Order By: Relevance
“…The slightly lower cholesterol efflux to apoA-I in the second hour here, compared with cholesterol efflux to apoA-I in untreated cells (third group from left), likely reflects the cholesterol depletion by st-Ht31 during the first hour. Furthermore, we found that st-Ht31 mainly stimulates the release of microparticles, similar to the ones we reported earlier by FPLC analysis (6). ABCA1 phosphorylation by PKA was not significantly altered, as probed by an antibody recognizing phosphorylated PKA substrates (Fig.…”
Section: St-ht31 Induces Robust Microparticle Release In the Absencesupporting
confidence: 75%
See 3 more Smart Citations
“…The slightly lower cholesterol efflux to apoA-I in the second hour here, compared with cholesterol efflux to apoA-I in untreated cells (third group from left), likely reflects the cholesterol depletion by st-Ht31 during the first hour. Furthermore, we found that st-Ht31 mainly stimulates the release of microparticles, similar to the ones we reported earlier by FPLC analysis (6). ABCA1 phosphorylation by PKA was not significantly altered, as probed by an antibody recognizing phosphorylated PKA substrates (Fig.…”
Section: St-ht31 Induces Robust Microparticle Release In the Absencesupporting
confidence: 75%
“…We presently do not understand the detailed cholesterol trafficking pathway that generates microparticles. These microparticles are uniform in size (Ͻ200 nm) and between 1.063 and 1.21 in density (6). We provide evidence here that these microparticles contain flotillin-2, an exosome marker and also a potential molecular module for exosome release (16).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It has been reported that ABCA1 mediates the formation of microparticles that are larger than HDL and are not involved in HDL formation ( 35,36 ). As previously reported, cholesterol-containing particles were observed in the conditioned medium from ABCA1-expressing cells around the void volume of the Superdex 200 column ( Fig.…”
Section: Detection Of Hdl Formation By Apoa-i-polaric In Abca1-expressupporting
confidence: 63%